Typing class I HLA-A gene using a nested PCR-RFLP procedure - Castelli, E.C. [UNESP]; Gil, D.S. [UNESP]; Veiga, L.C.S.; de Camargo, J.L.V. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2005)
In order to detect several new HLA-A class I alleles that have been described since 1998, the original PCR-RFLP method developed to identify the 78 alleles recognized at that time at high resolution level was adapted by us for low and medium resolution levels using a nested PCR-RFLP approach. The results obtained from blood samples of 23 subjects using both the PCR-RFLP method and a commercial kit (MicroSSP1A®, One Lambda Inc.) showed an agreement higher than 95%. The PCR-RFLP adapted method was effective in low and medium resolution histocompatibility evaluations.
Keywords: Human leukocyte antigen-A; HLA-A; Typing; RFLP; Polymorphism; Major histocompatibility complex